DESENVOLVIMENTO DE COMPÓSITOS A BASE DE POLIETILENO DE BAIXA DENSIDADE E NANOFIBRAS DE CELULOSE - AGNES, ERICK AFONSO (2022)
The growing demand for polymeric materials makes them significant both in industry and the environment, but it becomes more and more challenging for the industry to make them sustainable. Cellulose creates an opportunity to minimize the effect of non-degradable materials by using it as a reinforcement in thermoplastic matrices. NFC is part of a class of cellulose fibers with superior mechanical, thermal and optical performance to cellulose fiber, due to its high strength and rigidity combined with low weight and biodegradability. This work aimed to produce composites using Low Density Polyethylene (LDPE) as polymeric matrix and cellulose nanofiber (NFC) from Pinus and Eucalyptus as reinforcement. The NFCs were obtained by defibrillating the bleached cellulose in a Masuko MKCA 6-2 mill, after which excess water was removed by centrifugation. Then, a master was produced with NFC in a LDPE matrix using a Drais thermokinetic homogenizer. The master was milled and mixed with LDPE to obtain reinforcement concentrations of 1.0%, 2.0% and 3.0% by mass, using a twin-screw extruder, and subsequently pelletized. To characterize the composite, tensile, bending, thermal deflection temperature (HDT), thermal analysis (TGA DSC), gas permeability and rheological analysis were performed. The results showed an increase in the crystallinity of the composite with the addition of Pine NFC in the range of 3 to 4% and a reduction in the crystallinity index with the addition of Eucalyptus NFC in the range of 2 to 3%. Thermal stability increased for all compositions. Regarding the mechanical properties, it was observed that the increase in the NFC content increased the stiffness modulus and the tensile strength in relation to the LDPE, indicating the reinforcing action of the NFC. The composition with 3% Eucalyptus NFC did not show an increase in flexural strength property, although the elastic modulus increased. The charges were not efficient as a gas barrier. In general, it was found that the process is an effective alternative to produce composites of cellulose nanofibers in LDPE without the use of coupling agents.